Non-viral-mediated gene transfer of OX40 ligand for tumor immunotherapy - Rakitina, Olga A.; Kuzmich, Alexey I.; Bezborodova, Olga A.; Kondratieva, Sofia A.; Pleshkan, Victor V.; Zinovyeva, Marina V.; Didych, Dmitry A.; Sass, Aleksandr V.; Snezhkov, Eugene V.; Kostina, Maria B.; Koksharov, Maksim O.; Alekseenko, Irina V. (Frontiers in Immunology, 2024)
Background: Immune checkpoint blockade (ICB) is rapidly becoming a standard of care in the treatment of many cancer types. However, the subset of patients who respond to this type of therapy is limited. Another way to promote antitumoral immunity is the use of immunostimulatory molecules, such as cytokines or T cell co-stimulators. The systemic administration of immunotherapeutics leads to significant immune-related adverse events (irAEs), therefore, the localized antitumoral action is needed. One way to achieve this is intratumoral non-viral geneimmune therapy, which allows for prolonged and localized gene expression, and multiple drug administration. In this study, we combined the previously described non-viral gene delivery system, PEG-PEI-TAT copolymer, PPT, with murine OX40L-encoding plasmid DNA.The resulting OX40L/PPT nanoparticles were characterized via gel mobility assay, dynamic light scattering analysis and in vitro transfection efficiency evaluation. The antitumoral efficacy of intratumorally (i.t.) administered nanoparticles was estimated using subcutaneously (s.c.) implanted CT26 (colon cancer), B16F0 (melanoma) and 4T1 (breast cancer) tumor models. The dynamics of stromal immune cell populations was analyzed using flow cytometry. Weight loss and cachexia were used as irAE indicators. The effect of combination of i.t. OX40L/PPT with intraperitoneal PD-1 ICB was estimated in s.c. CT26 tumor model.The obtained OX40L/PPT nanoparticles had properties applicable for cell transfection and provided OX40L protein expression in vitro in all three investigated cancer models. We observed that OX40L/PPT treatment successfully inhibited tumor growth in B16F0 and CT26 tumor models and showed a tendency to inhibit 4T1 tumor growth. In B16F0 tumor model, OX40L/PPT treatment led to the increase in antitumoral effector NK and T killer cells and to the decrease in pro-tumoral myeloid cells populations within tumor stroma. No irAE signs were observed in all 3 tumor models, which indicates good treatment tolerability in mice. Combining OX40L/PPT with PD-1 ICB significantly improved treatment efficacy in the CT26 subcutaneous colon cancer model, providing protective immunity against CT26 colon cancer cells.Overall, the anti-tumor efficacy observed with OX40L non-viral gene therapy, whether administered alone or in combination with ICB, highlights its potential to revolutionize cancer gene therapy, thus paving the way for unprecedented advancements in the cancer therapy field.